Visual field indices and patterns of visual field deficits in mesopic and dark-adapted two-colour fundus-controlled perimetry in macular diseases - Pfau, M; Lindner, M; Steinberg, JS; Thiele, S; Brinkmann, CK; Fleckenstein, M; Holz, FG; Schmitz-Valckenberg, S (BMJ Publishing Group, 2017)
Background/Aims: To analyse the retest reliability of visual field indices and to describe patterns of visual field deficits in mesopic and dark-adapted two-colour fundus-controlled perimetry (FCP) in macular diseases. Methods: Seventy-seven eyes (30 eyes with macular diseases and 47 normal eyes) underwent duplicate mesopic and dark-adapted two-colour FCP (Scotopic Macular Integrity Assessment, CenterVue). Non-weighted (mean defect, loss variance), variability-weighted (mean deviation, pattern standard deviation (PSD)) and graphical (cumulative defect (Bebie) curves) indices were computed. Reproducibility (coefficient of repeatability, CoR) of these indices was assessed. Cluster analysis was carried out to identify patterns of visual field deficits. Results: The intrasession reproducibility was lower for the mean defect as compared with the mean deviation (CoR (dB) 2.67 vs 2.57 for mesopic, 1.71 vs 1.45 for dark-adapted cyan, 1.94 vs 1.87 for dark-adapted red testing) and lower for the square-root loss variance as compared with the PSD (CoR (dB) 1.48 vs 1.34, 0.77 vs 0.65, 1.23 vs 1.03). Hierarchical cluster analysis of the indices disclosed six patterns of visual field deficits (approximately unbiased P value>0.95) with varying degrees of global versus focal defect and rod versus cone dysfunction. These were also reflected by the cumulative defect curves. Conclusion: FCP with mesopic and dark-adapted two-colour testing allows for reproducible assessment of different types of retinal sensitivity, whereby mean deviation and PSD exhibited the better retest reliability of the tested indices. Distinct patterns of retinal dysfunction can be identified using this setup, reflecting variable degrees of rod and cone dysfunction in different macular diseases. Dark-adapted two-colour FCP provides additional diagnostic information and allows for refined structure–function correlation in macular diseases.